2007
DOI: 10.1097/mlg.0b013e31802c300c
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Endolymphatic Hydrops in Patients With Meniere's Disease

Abstract: We reported the first visualization of endolymphatic hydrops in patients with Meniere's disease. The relationship between the image of the endolymphatic space and functional tests, such as electrocochleography and vestibular-evoked myogenic potential, must be examined in the near future. It is important for the development of intratympanic drug therapies for inner-ear diseases to investigate how the drugs enter and leave the inner ear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
357
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 530 publications
(369 citation statements)
references
References 15 publications
2
357
0
10
Order By: Relevance
“…23 Recent studies using magnetic resonance imaging have also confirmed these histopathologic findings. 24,25 In the Surgery group in Experiment 1, ears that underwent electrocauterization of the ES but without administration of desmopressin developed slight to moderate hydrops, indicating that prolonged ES dysfunction induced by electrocauterization may cause malabsorption of endolymph, and thus development of EH. This assumption is in line with following histopathologic findings related to the ES in patients with MD: poor development of the ES, 26,27 fibrotic changes of the ES, and a hypoplastic vestibular aqueduct.…”
Section: Discussionmentioning
confidence: 99%
“…23 Recent studies using magnetic resonance imaging have also confirmed these histopathologic findings. 24,25 In the Surgery group in Experiment 1, ears that underwent electrocauterization of the ES but without administration of desmopressin developed slight to moderate hydrops, indicating that prolonged ES dysfunction induced by electrocauterization may cause malabsorption of endolymph, and thus development of EH. This assumption is in line with following histopathologic findings related to the ES in patients with MD: poor development of the ES, 26,27 fibrotic changes of the ES, and a hypoplastic vestibular aqueduct.…”
Section: Discussionmentioning
confidence: 99%
“…18 High sensitivity to subtle T 1 changes in fluid FLAIR is reported to be more sensitive to subtle T 1 changes in fluid than conventional T 1 -weighted images. [21][22][23][24][25][26][27][28][29][30] A FLAIR image allows the detection of subtle subarachnoid hemorrhage in the CSF space, 9 signal increases in CSF after the inhalation of oxygen, 31 and subtle compositional changes of the labyrinthine fluid (Figs. 6 and 7), 26,27,30,[32][33][34] which can be difficult to recognize on T 1 -weighted images.…”
Section: T 2 -Selective Inversion Recoverymentioning
confidence: 99%
“…Patients received a dose of 8-fold diluted gadopentetate dimeglumine (Magnevist, Bayer Co. Ltd., Osaka, Japan) in one ear 24 hours prior to MR scanning according to the procedure previously detailed for IT injection. 9 Our medical ethics committee approved the use of the IT method for GBCM administration, and all patients gave written informed consent. The committee also approved this retrospective analysis of data using the IT and IV methods and waived informed consent.…”
Section: Mr Imagingmentioning
confidence: 99%
“…[7][8][9] A specific size criterion for the diagnosis of endolymphatic hydrops has been proposed for the inner ear without significant morphological anomaly. 10 According to this criterion, endolymph occupying more than half of the total vestibular space is defined as significant endolymphatic hydrops.…”
Section: Introductionmentioning
confidence: 99%